Chloride intracellular channel 1 regulates the antineoplastic effects of metformin in gallbladder cancer cells. Issue 6 (22nd May 2017) - Liu, Yongchen; Wang, Zheng; Li, Maolan; Ye, Yuanyuan; Xu, Yi; Zhang, Yichi; Yuan, Ruiyan; Jin, Yunpeng; Hao, Yajuan; Jiang, Lin; Hu, Yunping; Chen, Shili; et al.
Abstract : Metformin can exhibit antineoplastic effects on gallbladder cancer cells. Membrane protein Chloride intracellular channel 1(CLIC1) can affect GBC resistance in the presence of metformin. Abstract : Metformin is the most commonly used drug for type 2 diabetes and has potential benefit in treating and preventing cancer. Previous studies indicated that membrane proteins can affect the antineoplastic effects of metformin and may be crucial in the field of cancer research. However, the antineoplastic effects of metformin and its mechanism in gallbladder cancer (GBC) remain largely unknown. In this study, the effects of metformin on GBC cell proliferation and viability were evaluated using the Cell Counting Kit‐8 (CCK‐8) assay and an apoptosis assay. Western blotting was performed to investigate related signaling pathways. Of note, inhibition, knockdown and upregulation of the membrane protein Chloride intracellular channel 1 (CLIC1) can affect GBC resistance in the presence of metformin. Our data demonstrated that metformin apparently inhibits the proliferation and viability of GBC cells. Metformin promoted cell apoptosis and increased the number of early apoptotic cells. We found that metformin can exert growth‐suppressive effects on these cell lines via inhibition of p‐Akt activity and the Bcl‐2 family. Notably, either dysfunction or downregulation of CLIC1 can partially decrease the antineoplastic effects of metformin while upregulation of CLIC1 can increase drug sensitivity. Our findings provide experimental evidence for using metformin as an antitumor treatment for gallbladder carcinoma.